UNFOLDING TRANSLATION STRATEGY AND IDEOLOGY IN LITERARY WORK - Muajiz Muallim; Mujahidah; Resneri Daulay (Inspiring: English Education Journal, 2023)
Translation has now become subject matter since its role as cross-culture and cross-language mediator. This research, then, aims to unfold the translation strategy and ideology reflected in literary work. The data source are the American short story “The Lottery“ written by Shirley Jackson and its Indonesian version “Undian“ translated by Harum L Wibowo. This research employ qualitative approach and descriptive method. Both of the strategy of literary translation theory by Kazakova (2015) and translation ideology theory by Venutti (1994) are used to answer the question of the research. This research found that translator used all four strategies of literary translation proposed by Kazakova; helper strategy (35,57%), observer strategy (26,17%), enlightener strategy (20,13%), and adherent strategy strategy (18,12%). It also found that the strategy used by translator alternately applied both foreignization and domestication ideology on his translation process. Thus, while preserving the foreign culture and language, the translator also adapt ST/SL into TT/TL in his translation process to make it fluent to the target reader.